Effects of enzyme treatment and shell content of palm kernel expeller on performance and nutrient digestibility in broilers - Jahromi, Mohammad Faseleh; Navishad, B.; Liang, Juan Boo (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
One hundred day-old male broiler chicks were allocated to 20 pens. At 29-42 d, the birds were fed one of the five experimental finisher diets: palm kernel expeller (PKE) free diet (control) and four experimental diets containing 200 g/kg of normal PKE, low shell PKE, enzymatic treated PKE or low shell-enzymatic treated PKE. Enzyme treatment increased mannose content drastically followed by glucose and xylose. Enzyme treatment also increased the mannan-oligosaccharides content in PKE with mannobiose made up the major component. Surprisingly, the average daily weight gain and feed conversion ratio of the birds fed low shell PKE diet was inferior than those in the control and other PKE treatment groups. Digestibility of dry matter, ash and crude protein in diets containing PKE were lower than the control diet. The lower growth rate in chicks fed low shell PKE containing diet could be because of the increased β-mannan concentration in this product when the shell was removed.